Android Mobile Malware Classification using Tokenization Approach based on System Call Sequence - Ahmad, IN; Ridzuan, F; Nabila, NF; Madihah Mohd Saudi; Sakinah Ali Pitchay; Nurlida Basir (Int Assoc Engineers-Iaeng, 2024)
The increasing number of smartphone over the last few years reflects an impressive growth in the number of advanced malicious applications targeting the smartphone users. Recently, Android has become the most popular operating system opted by users and the most targeted platform for smartphone malware attack. Besides, current mobile malware classification and detection approaches are relatively immature as the new advanced malware exploitation and threats are difficult to be detected. Therefore, an efficient approach is proposed to improve the performance of the mobile malware classification and detection. In this research, a new system call classification with call logs exploitation for mobile attacks has been developed using tokenization approach. The experiment was conducted using static and dynamic-based analysis approach in a controlled lab. System calls with call logs exploitation from 5560 Drebin samples were extracted and further examined. This research paper aims to find the best n value and classifier in classifying the dataset based on the new patterns produced. Naive Bayes classifier has successfully achieved accuracy of 99.86% which gives the best result among other classifiers. This new system call classification can be used as a guidance and reference for other researchers in the same field for security against mobile malware attacks targeted to call logs exploitation.